Estrategias metodológicas en el área de matemática y su incidencia en el rendimiento académico de los estudiantes del subnivel básica elemental en el periodo 2016-2017 - Vaca Salas, Bárbara Daniela (2017)
The present research has the objective to investigate the methodological strategies at the area of mathematics because it is topic of great importance, due to the incidence in the academic performance of the students; These are integrated sequences of procedures and resources used by the trainer with the purpose to developi learners capacities for acquisition, interpretation and information processing and the use of these in the generation of new knowledge, its application on different areas where they perform, as well as in daily life in order to promote meaningful learning. The research work is born of the problematic that the students of the Basic Education School "23 de Julio" have on the mathematics learning and the use of some innovativing methodological strategies that will allow to improve the academic performance to impel the teachers of each basic year to promote on students the ability to pose and solve problems with a variety of strategies, active methodologies and resources, not only as an application tool, but also as a basis for the general approaching to work at all stages of the process of teaching-learning in the area of mathematics. This research at the end will generate a practical contribution that consists about how is affecting the methodological strategies in the academic performance of students that will allow a future to develop strategies to increase this performance which would get a social impact, since mathematics is one of the sciences of great relevance in the educational process due the interrelation that exists between it and other disciplines, for its aid to the logical and systematic thought. The research modality used is quantitative it means, it is worked with statistical data collected on the basis of the applied survey, corresponds to the type of exploratory and field researching, since, important characteristics were determined on the methodological strategies on mathematics area and their impact on academic performance, in addition, the survey technique was used with its respective data collection instruments. It was worked with a population made up of 64 students belonging to Elementary Basic Education and 7 teachers from the above- mentioned campus.